Evaluation of single and multiple doses of a novel mGlu2 agonist, a potential antipsychotic therapy, in healthy subjects. (31st March 2017) - McColm, Juliet; Brittain, Claire; Suriyapperuma, Subha; Swanson, Steven; Tauscher‐Wisniewski, Sitra; Foster, Joanne; Soon, Danny; Jackson, Kimberley
Abstract : Aims: The safety, tolerability, pharmacokinetics (PK) and pharmacodynamics of single and multiple doses of a novel mGlu2 agonist were assessed in healthy males. Methods: In two, Phase 1 investigator‐ and subject‐blind, placebo‐controlled studies, oral doses of prodrug LY2979165 were evaluated: single doses (20–150 mg, N  = 30) and multiple once‐daily (QD) doses (20–400 mg; N  = 84), using a titration regimen. The plasma and urine PK of LY2979165 and active moiety, 2812223, were measured. Cerebrospinal fluid (CSF) was collected to determine PK and neurotransmitter levels. Safety parameters were assessed throughout. Results: Nausea and vomiting were dose limiting following single doses; dose titration allowed higher doses to be tested over 14 days. The most common adverse events related to LY2979165 were dizziness, vomiting, nausea, somnolence and headache. The plasma PK of 2812223 were approximately linear with minimal accumulation with QD dosing. Conversion of LY2979165 to 2812223 was extensive, with minimal LY2979165 measurable in plasma. There was no effect of food on the PK of LY2979165 and 2812223. After 60 mg LY2979165 single‐dose, 2812223 exposure in CSF was approximately 2–6% and plasma exposure and peak concentrations were approximately four‐fold higher than the mGlu2 agonist in vitro EC50 value. No consistent effects were observed on CSF neurotransmitter levels. Conclusions: Oral doses of LY2979165 up to 60 mg as a single dose and up to 400 mg given as multiple QD doses, using a titration regimen, were well tolerated with linear PK. Overall, these data support further clinical evaluation of LY2979165.